Existence of Solutions to a Semilinear Elliptic System Through Generalized Orlicz-Sobolev Spaces (Journal of Partial Differential Equations, 2010)
This paper is concerned with the existence theory of a semilinear elliptic system. In particular, we will prove that the system has a nontrivial positive solution in some appropriate solution spaces.